So, how old is too old: A forced reflection on the meaning of old age - Sellers, Debra M. (My University, 2009)
This first person narrative details an illuminating and personal insight that transpired for the author, a gerontologist. Her attitudes about growing older, the meaning of old age, and implicit ageist views are challenged during a chance encounter. This insight occurred in the most unlikely place—a racetrack—and during a time when she was certainly “off duty” as a gerontologist and thus, perhaps, most unprepared for the consequences of the interaction. The author is forced to reflect upon her own life and old age future, and is able to find serenity and peace in that vision.
Keywords: Ageism; Attitudes; Old age